Creative and Innovative Digital Economy Training to Increase Income of SMA Karya Utama Students - Praja Anggriany Panggabean, Esther; Sri Astuti Doloksaribu, Winda; Batubara, Maisara; Natalia Pasaribu, Lidya; Intan Purba, Mas; Endah Ndilosa Ginting, Kristi; Fitria, Fariza (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Abstract: The creative and innovative digital economy, fuelled by digital technology and the internet, offers numerous opportunities for individuals to increase their income. Shopee, a widely recognised e-commerce platform, effectively taps into this potential with its user-friendly services. SMA Karya Utama, a 22-student senior high school located at Jalan Pendidikan No. 23 Marindal Village, Patumbak District, has yet to fully comprehend the potential of e-commerce for entrepreneurship, as evidenced by the PKM team's survey. To bridge this gap, the PKM team aims to educate SMA Karya Utama students on the opportunities presented by the digital economy and how to utilise the Shopee app for sales. The PKM activity employed a variety of socialisation, demonstration, and practical methods to expose students to creative digital economy concepts and train them in the operational aspects of Shopee. The results of this activity included increased knowledge of the digital economy and practical skills in account creation, product uploading, store management, and marketing on Shopee. The training aimed to empower SMA Karya Utama students to increase their income, foster independence, and equip them to effectively face future economic challenges. Keyword: Digital Economy, Shopee, SMA Karya Utama, Student Income